Design theory to better target public health priorities: An application to Lyme disease in France - Vourc'h, Gwenaël; Un, Katherine; Berthet, Elsa; Frey-Klett, Pascale; Le Masson, Pascal; Weil, Benoit; Lesens, Olivier (Frontiers in Public Health, 2022)
In the context of complex public health challenges led by interdependent changes such as climate change, biodiversity loss and resistance to treatment, it is important to mobilize methods that guide us to generate innovative interventions in a context of uncertainty and unknowns. Here, we mobilized the Concept-Knowledge (CK) design theory to identify innovative, cross-sectoral and cross-disciplinary research and design programs that address the challenges posed by tick-borne Lyme disease in France, which is of growing importance in the French public health and healthcare systems. Within the CK methodological framework, we developed an iterative approach based on literature analysis, expert interviews, analysis of research projects and work with CK experts to contribute to design “an action plan against Lyme disease”. We produced a CK diagram that highlights innovative concepts that could be addressed in research projects within four directions: (i) effectiveness and (ii) environmental sustainability in prevention actions; (iii) the promotion of constructive involvement of citizens in Lyme challenges; (iv) the development of care protocols for chronic conditions with unknown diagnosis. Altogether, our analysis questioned the health global objectives from population to ecosystem, the citizen involvement and the patient consideration. This means integrating social and ecological science from the start as well as multidisciplinary medical patient journey. CK theory is a promising frame to assist public health professionals in designing programs for complex yet urgent contexts, where research and data collection are still not sufficient to provide clear guidance.